Other Experts: Disciplinary and Aesthetic Impacts of Artificial Intelligence. (1st September 2020) - Rehm, M Casey
Abstract: Constrained artificial intelligence can provide many benefits to the building industry of the 21st century. Los Angeles‐based multidisciplinary designer and SCIArc tutor M Casey Rehm describes how AI, programmed without a priori concepts, can develop many previously inconceivable architectural solutions. Such designs do not depend on traditional or received human thought patterns.